2019
DOI: 10.2196/10348
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Internet Use and Its Association With Patient Decision Making and Trust in Physicians Among Patients in an Early Drug Development Clinic: A Questionnaire-Based Cross-Sectional Observational Study

Abstract: Background The role of cancer-related internet use on the patient-physician relationship has not been adequately explored among patients who are cancer-related internet users (CIUs) in early-phase clinical trial clinics. Objective We examined the association between cancer-related internet use and the patient-physician relationship and decision making among CIUs in an early drug development clinic. Methods Of 291 Phase I clinic patients who c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Patients will inevitability search the internet for information related to risk upon reading a mammographic report detailing their risk, and possibly before they have a chance to discuss with their provider. Nearly 77% of adults are known to browse online for health-related topics [ 6 ] and approximately 89% of patients are known to browse online directly following a cancer diagnosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients will inevitability search the internet for information related to risk upon reading a mammographic report detailing their risk, and possibly before they have a chance to discuss with their provider. Nearly 77% of adults are known to browse online for health-related topics [ 6 ] and approximately 89% of patients are known to browse online directly following a cancer diagnosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other survey questions regarding demographics, duration of time in current early‐phase clinical trial, and how patients paid for their current treatment were based on the experience of the study investigators regarding developing surveys for patients in early‐phase clinical trials [17] and extant literature on financial toxicity [2, 18]. An initial pilot group was asked for feedback to ensure appropriate usability.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Telehealth, or the use of technology-including the internet and mobile phones-to enable or improve health or health care [4,5], has expanded in scope and capabilities in recent decades. Patients can now access personal health information through patient portals [6], look up health information independently without professional medical guidance [7][8][9][10][11], and provide feedback to other consumers on their experiences with certain hospitals or providers through these media [12]. Studies have shown that the use of technology in the health sector can improve intervention efficacy, patient satisfaction, and, ultimately, clinical outcomes [13][14][15][16][17].…”
Section: Introduction Backgroundmentioning
confidence: 99%